1988
DOI: 10.1002/1097-4679(198811)44:6<907::aid-jclp2270440610>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in verbal learning

Abstract: Although sex differences in cognitive abilities have been reported in the experimental literature, there has been a paucity of information about how men and women might perform differently on clinical neuropsychological tests. The present study examines sex differences in verbal learning. Sixtyeight men and 68 women of equal age and education were administered the California Verbal Learning Test. Dependent variables included measures of recall, recognition, learning characteristics, and error types. Women disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
123
7
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(152 citation statements)
references
References 38 publications
19
123
7
3
Order By: Relevance
“…Here, we found that the female group had lower lateralization of the direct segment and slightly better performances in the CVLT compared with males (SI Table 3). Kramer et al (46) have demonstrated that females tend to outperform males on recall measures of this test. However, our findings of better performances of Group 2 over Group 1 in both genders (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Here, we found that the female group had lower lateralization of the direct segment and slightly better performances in the CVLT compared with males (SI Table 3). Kramer et al (46) have demonstrated that females tend to outperform males on recall measures of this test. However, our findings of better performances of Group 2 over Group 1 in both genders (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…This differs from some reports of less neurocognitive impairment in women than men with schizophrenia (Goldstein et al 1998;Hoff et al 1996), or more impairment in women than men (Lewine et al 1996), but is consistent with earlier reports from our center reporting similar impairment in male and female patients. The difference favoring women with schizophrenia for verbal memory and men for spatial processing may reflect normal sex differences in these domains (Bleecker et al 1988;Gur et al 1999aGur et al ,2001Kimura and Harshman 1984;Kramer et al 1988). Thus, it seems that although clinical measures favoring women do correlate with neurocognitive functioning, the effect is not sufficient to produce a group difference in neuropsychological performance.…”
Section: Study 2: Discussionmentioning
confidence: 99%
“…Words mentioned early in the sequence are remembered best followed by words presented last; with middle items recalled to a lesser extent (Graf & Uttl, 1995). Whereas learning curves in these tasks usually increase from around seven words in the first trial to 13 words in the fifth trial (Bleecker, Bollawilson, Agnew, & Meyers, 1988;Kramer, Delis, & Daniel, 1988), non-word recall in our study increased from around three to eight items over the five acquisition trails. This finding clearly confirms that the CVC is unlikely to display ceiling effects.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to gender, women generally recall more words, but have a similar learning curve to men (Kramer et al, 1988;Reite, Cullum, Stocker, Teale, & Kozora, 1993). The difference in recall is on average one word more per trial (Kramer et al, 1988).…”
Section: Discussionmentioning
confidence: 99%